KEMAMPUAN BELAJAR MEMPENGARUHI MOTIVASI BELAJAR MAHASISWA DI AKADEMI KEPERAWATAN HERMINA MANGGALA HUSADA JAKARTA - Ria Anugrahwati, Junita Silitonga (Institut Kesehatan Hermina, 2020)
Motivation to learn is a driving force in students that ultimately raises the desire to learn so that goals are achieved. Learning motivation is supported by the ability to learn to make it easier to absorb knowledge. This study aims to see the student's learning ability can influence learning motivation. This study used a cross sectional study survey design on 100 student respondents. The resultsshowed the ability to learn affects student motivation. The recommendation of this research is the need for good communication between lecturers and students related to learning motivation to increase student activities by means of discussion between friends and lecturers in terms of learning so that students will be motivated properly.